A Scoping Review and Psychometric Assessment of Survey Instruments Used to Evaluate Post-secondary Student Stress - Linden, Brooke; Diana-Gonsalves, Claire (Journal of psychoeducational assessment, 2025)
Post-secondary students are exposed to a wide variety of stressors, and mental health-related concerns continue to increase among this population. The development and improvement of mental health services hinges on the use of valid and reliable measurement tools to assess student stress and evaluate the efficacy of interventions. To date, there has been no comprehensive overview of available instruments intended to evaluate post-secondary student stress. The purpose of this study was to conduct a rigorous scoping review of published works detailing the use of instruments to evaluate post-secondary student stress, and evaluate the psychometric properties of these tools as well as their suitability for use among post-secondary populations. Four academic databases were searched, including HaPI, CINAHL, Medline, and PsycINFO, including peer-reviewed records published in English between 2012 and 2024. Articles were independently screened for inclusion by title, abstract, and full-text review. A total of 62 records and 11 instruments were screened into the review. The majority of instruments included in our review did not meet the criteria for suitability, nor did they have published, comprehensive psychometric evaluations. The Post-Secondary Student Stressors Index emerged as the most appropriate instrument for evaluating post-secondary student-specific stress owing to both its suitability and strong psychometric properties. The Perceived Stress Scale and Stress Overload Scale were deemed to be the most appropriate instruments for evaluating general stress levels.